Influence of concentration of sugar on mass transfer of pineapple slices during osmotic dehydration (Journal of the Bangladesh Agricultural University, 2014)
Osmotic drying is a partial dehydration process to give the product a quality improvement over the conventional drying process. The experiment was conducted for studying water loss(WL), sugar gain(SG), weight reduction(WR) and total solid(TS) during osmotic dehydration of pineapple slices (10 mm thick) in different concentration of sugar (40%, 50% and 60%) up to 6 hours at room temperature. It was found that increasing the concentration of the sugar solution used resulted in increased rates of water loss. The water loss at 40% sugar solution of pineapple slices were found to be significantly lower (p=0.05) than that of at 60% sugar solution. It was found there were rapid rates of water loss, sugar gain, weight reduction for first four hour of the osmotic process. DOI: http://dx.doi.org/10.3329/jbau.v12i1.21415 J. Bangladesh Agril. Univ. 12(1): 221-226, June 2014